PENGGUNAAN ASPEK TE IRU PADA SAKUBUN MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Annisa Qamara Tasman; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Te iru is one aspect of Japanese. This research discusses the usage of te iru aspects in the sakubun of 2019 college students Japanese Language Education Study Program of Teachers Training and Education Faculty Riau University. The purpose of this study is to find out how usage te iru in sakubun of 2019 college students. The method used in this study is qualitative descriptive by observing sakubun documentation from 8 students. The results showed that usage of te iru in progressive and resultive aspects was not very visible because that aspect's situation, meanwhile the usage of te iru appeared in the habituative aspect but college students did not use te iru in the sakubun.Key Words: Usage, Aspect, Te Iru, Sakubun